Penetration of Radial nerve by subscapular artery - Kuwar, RB; Basnet, KS; Dhungel, S; Thapa, TP (Journal of Institute of Medicine Nepal, 2010)
The present case report is about an abnormal radial nerve which was penetrated by Subscapular artery, the largest branch of Axillary artery. The nerve was completely divided into two parts; one passing posterior and the other anterior to the subscapular artery, clasping it between them. However, on due course, both parts of the nerve united together to form single radial nerve in the lower part of Axilla. Key Words: Axillary artery, brachial plexus, radial nerve, subscapular artery, posterior cord. The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, August, 2009; 31:2 37-38